Perpustakaan Audiovisual Digital Menggunakan Streaming Open Source - Agung, I Putu Suhada (Seni Media Rekam ISI Surakarta, 2015)
Indonesian Institute of the Arts Surakarta has a unique library when compared to other universities. In addition to print collection, there is also a collection of audio and audiovisual. During this time, user still using the manual technology for use it. The computers technology can be an alternative solution to overcome the existing problems. The trick is to use a computer server that can accommodate all the collections, in addition to also use as a workstation computer library service providers. With this technology, users can use the digital library service that is fast, easy, and efficient. Open source technology in streaming software was chosen to embody the digital library.Keywords : library, collection, server, and streaming